Penerapan Fingerprint dalam Meningkatkan Karakter Disiplin Siswa di SMA Negeri 1 Luragung - Merliyani, Siska; Zakaria, Yoyo (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of the study was to analyze how the effectiveness of the implementation of fingerprint attendance at SMAN 1 Luragung on improving the character of student discipline at SMAN 1 Luragung. The method used in this study is a qualitative method with a qualitative design of a descriptive type. The research participants were 10 students in grade XI. The data collection technique uses interviews, observations, and documentation while the instrument used is an interview sheet. Data analysis techniques by means of data reduction, data presentation and verification or conclusion drawing. The results of the study show that the use of fingerprint attendance at SMA Negeri 1 Luragung is generally quite effective. This technique helps create a more organized and comfortable learning environment by improving student discipline and attendance management in general. The level of student attendance discipline at SMA Negeri 1 Luragung has increased significantly. Students become more responsible, punctual, and understand that discipline is the key to success, both in school and in everyday life. The implementation of the fingerprint system at SMA Negeri 1 Luragung has a significant effect on improving the character of student discipline. This system makes students more aware of the importance of responsibility and punctuality, thereby reducing the rate of tardiness and absenteeism.